Dealing with Loneliness in Hemodialysis Patients: How to Prevent the Detrimental Effects of Loneliness - Hendy Muagiri Margono (Jurnal Psikiatri Surabaya, 2024)
Introduction: Chronic Renal Failure (CRF) refers to advanced, irreversible, and progressive renal failure. Existing treatment for CRF patients includes hemodialysis (HD), peritoneal dialysis, and kidney transplantation. HD is the most common replacement therapy for kidney function. HD patients often experience severe psychological problems such as anxiety, depression, loneliness, and many difficulties related to stress and unhealthy coping mechanisms. To describe preventive actions against the detrimental effects of loneliness in HD patients. Methods: Literature review. Results: The feeling of loneliness is always annoying and unwanted. Loneliness may limit human development and interfere with normal functioning. It is associated with a sense of hopelessness, abandonment or boredom, reduced self-esteem, alienation, an external sense of control and aggression, depression, hostility, and even suicidal tendencies. Feelings of sadness, loneliness, and fatigue are significant factors in reducing patient treatment adherence and even lead to premature death. Conclusions: It is paramount to cope with disease-related stress and anxiety in healthy ways. Comprehensive psychosocial intervention in HD patients could bring positive impacts on mental well-being to strengthen their sense of self, overcome loneliness, connect with others, and create good resilience for having to live with their chronic illness. Keywords: Loneliness, Hemodialysis, Psychosocial Intervention.